Diagnosis and prevention of rabbit viral haemorrhagic disease 2. Issue 1 (27th January 2018) - Rocchi, Mara S.; Dagleish, Mark P.
Abstract : Rabbit haemorrhagic disease (RHD) is a highly infectious, often fatal, disease of rabbits and it is commonly found throughout the UK. RHD is caused by rabbit haemorrhagic disease virus (RHDV), also known as rabbit calicivirus (RCV). Since 2010, a new virus variant (RHDV2/RHDVb) emerged in Europe, and was identified in the UK in 2014; this new variant has now replaced the original virus in many countries. This article discusses the diagnosis and prevention of RHDV2 and the resources, such as diagnostic laboratories and vaccines, currently available in the UK.